Surgical Treatment of Hemorrhoids - Khubchandani, Indru.; Paonessa, Nina.; Azimuddin, Khawaja. (Springer London : Imprint: Springer, 2009)
Following on from the hugely successful Surgical Treatment of Hemorrhoids, the second edition not only updates on information from the previous edition, but also has the added bonus of extra material such as the inclusion of specialist knowledge on recent innovations in the area of hemorrhoid treatment. Surgical Treatment of Hemorrhoids 2e is a high level text covering both recent advances and traditional treatments in this field. The topics covered include essential elements of diagnosis, surgical technique and after-care for the main operations used in hemorrhoid surgery. Providing authoritative in-depth presentations of all perspectives and latest techniques available, the individual procedures are each described by an internationally recognised expert, and the full range of treatment options is covered. Additions and updates to the list of chapters makes this edition a fully up-to-date volume and includes stapled hemorrhoidectomy and office management, and hemorrhoidectomy with several concomitant comorbidities. Surgical Treatment of Hemorrhoids 2e covers an important and common disorder, offering a comprehensive critical analysis of advantages and disadvantages of recognized treatment options. The result is a uniquely comprehensive guide which will prove invaluable to both trainee and practising colorectal and general surgeons.